INTERNATIONAL DIPLOMACY IN ISLAMIC RELIGION: HISTORY AND MODERNITY (American Journal of Interdisciplinary Research and Development, 2022)
This article describes some aspects of the Islamic factor in international relations and diplomacy in history and modernity, through the prism of geopolitics, Islamic studies, oriental studies and through the use of scientific results of domestic and foreign researchers